2019
DOI: 10.1590/1676-0611-bn-2019-0742
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between cetaceans and artisanal fishermen from Ilhéus, Bahia - Brazil

Abstract: Ethnobiological studies are necessary to understand the relationships between fishers and cetaceans. The aim of this study was to describe the interactions between cetaceans and artisanal fishers and the possible conflicts that can arise as a result. Semi-structured interviews were conducted from February to September 2017 with 35 fishermen from the municipality of Ilhéus, Brazil. All fishermen reported both positive and negative interactions with Megaptera novaeangliae, Tursiops truncatus and Sotalia guianens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Studies of spatiotemporal factors have identified peak areas of depredation associated with strong overlaps between natural foraging grounds of predators and fishing operations (González et al, 2015;Nitta & Henderson, 1993;Seminara, Barbosa-Filho, & Pendu, 2019;Stepanuk et al, 2018;Wickens, 1995) and/or distances from haul-out sites for pinnipeds (Cronin, Jessopp, Houle, & Reid, 2014;Hückstädt & Antezana, 2003). Similarly, peak in depredation were associated with seasonal variation in species co-occurrence with fisheries due to their phenology (reproduction or migrations) (Bombau & Szteren, 2017;De María, Barboza, & Szteren, 2014;Janc et al, 2018).…”
Section: Quantifying the Determinants Of Depredationmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of spatiotemporal factors have identified peak areas of depredation associated with strong overlaps between natural foraging grounds of predators and fishing operations (González et al, 2015;Nitta & Henderson, 1993;Seminara, Barbosa-Filho, & Pendu, 2019;Stepanuk et al, 2018;Wickens, 1995) and/or distances from haul-out sites for pinnipeds (Cronin, Jessopp, Houle, & Reid, 2014;Hückstädt & Antezana, 2003). Similarly, peak in depredation were associated with seasonal variation in species co-occurrence with fisheries due to their phenology (reproduction or migrations) (Bombau & Szteren, 2017;De María, Barboza, & Szteren, 2014;Janc et al, 2018).…”
Section: Quantifying the Determinants Of Depredationmentioning
confidence: 99%
“…For instance, multi‐variate statistical analyses highlighted times of year or areas of high probability of depredation for pinnipeds (e.g. Cosgrove et al, 2015; González, Vega, & Yáñez, 2015; Pon et al, 2012), for odontocetes (e.g. Cruz, Menezes, Machete, & Silva, 2016; Goetz, Laporta, Martinez Portela, Santos, & Pierce, 2011; Hernandez‐Milian et al, 2008; Muñoz‐Lechuga, Rosa, & Coelho, 2016; Passadore, Domingo, & Secchi, 2015; Pennino, Rotta, Pierce, & Bellido, 2015; Rocklin et al, 2009; Söffker et al, 2015; Tixier, Burch, et al, 2019; Tixier, Giménez, et al, 2019) and for sharks (e.g.…”
Section: Mitigation Attemptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these methods to engage with fishers can improve the relationship between fisheries and research institutes and can therefore lead to increased data and better fisheries management (Johnson and Densen, 2007). This method has been used to study experiences and effects of whale depredation on fisheries in Alaska, USA (Peterson and Carothers, 2013), seal-fisheries interactions in Greece and Cornwall, England (Glain et al, 2001), gear damage caused by whales and sharks in Newfoundland and Labrador, Canada (Lien and Aldrich, 1982), fisher knowledge of marine megafauna bycatch off Mayotte Island, Mozambique (Pusineri and Quillard, 2008), cetacean-fisheries interaction in Galicia, Spain (Goetz et al, 2014) and Bahia, Brazil (Seminara et al, 2019) and marine mammal bycatch in the South China Sea (Liu et al, 2016), Victoria, Australia (Norman, 2000), Northwest Spain (López et al, 2003), artisanal fisheries in African, Asian and Caribbean countries (Moore et al, 2010) and Iceland (Ólafsdóttir, 2010). Surveys of fishers and onboard observation can be useful tools to collect eye-witness accounts of whale-gear interactions and specific details of these incidents that cannot be inferred using conventional methods of studying whale entanglements (Knowlton et al, 2005).…”
Section: Introductionmentioning
confidence: 99%